Penggunaan Telehealth atau Telenursing di Indonesia selama Pandemi COVID-19 - Shafira Amalia Putri; Agus Sudaryanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to find the literature that discusses telehealth or telenursing in Indonesia during the COVID-19 pandemic. The method used in writing is a literature review. The study results in show that telehealth benefits patients and health service providers by increasing the knowledge of medical staff and updating knowledge to improve the health services provided. The health promotion offered can be carried out more optimally, and with this telehealth, nurses can monitor the patient's condition to determine whether the behavior is under the health promotion offered. In conclusion, telehealth can be used as a solution in remote care to limit direct contact. The use of telehealth or telenursing has a very positive impact. Patients can only complete treatment by telephone, computer, internet, video, and audio conferencing. The time spent in remote care is also quite effective. Keywords: COVID-19 pandemic, Telehealth, Telenursing